Security Defense Technology in the Technology Transfer Program (ToT) by the Defense Industry For Support National Security - Lutvie, Eko; Aritonang, Sovian; Aperiawan, Gita; Jupriyanto, Jupriyanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Technology Transfer Program (ToT) in the sector defense aiming For strengthen capability military and guard state sovereignty through mastery previous technology owned by other countries. In the ToT program , the aspects security technology is very important For ensure that technology adopted defense No prone to to threat or leakage information. This article analyzing security strategies technology in the ToT program in the sector defense, including identification risk , implementation policy security, and its impact to security national . Research results show that implementation standard strict security on ToT program can increase Power competition defense, but also requires cooperation between institution For guard confidentiality and effectiveness technology.